2008
DOI: 10.1590/s0100-204x2008000900012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and nitrogen fixation capacity of Rhizobium strains on common bean

Abstract: -This study aimed to genetically characterize four new Rhizobium strains, and to evaluate their nodulation and fi xation capacity compared to commercial strains and to native rhizobia population of a Brazilian Rhodic Hapludox. Two experiments were carried out in randomized blocks design, under greenhouse conditions, in 2007. In the fi rst experiment, the nodulation and nitrogen fi xation capacity of new strains were evaluated, in comparison to the commercial strains CIAT-899 and PRF-81 and to native soil popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Greater values of N-Total were observed to the nitrogen treatments. Similar results reported by Gonzáles et al 41 in a field experiment showed that nitrogen treatment resulted in greater N-Total compared to inoculation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Greater values of N-Total were observed to the nitrogen treatments. Similar results reported by Gonzáles et al 41 in a field experiment showed that nitrogen treatment resulted in greater N-Total compared to inoculation.…”
Section: Discussionsupporting
confidence: 89%
“…Measurements of SDM and LA provide important information about plant growth 38 because these parameters are good indicators of plant nutritional status, which has a direct influence on crop production 39, 40. Moreover, this approach has been used for strain selection to compose bacterial inoculants 40, 41…”
Section: Discussionmentioning
confidence: 99%